Continuity of operator-valued functions in the *-algebra of locally measurable operators - Muratov, M. A.; Chilin, V. I. (Methods of Functional Analysis and Topology, 2014)
In the present paper we establish sufficient conditions for a complex-valued function f defined on R which guarantee continuity of an operator-function Tf(T) w.r.t. the topology of local measure convergence in the *-algebra LS(M) of all locally measurable operators affiliated to a von Neumann algebra M.